مقارنة أداء منهجيتي Arima وfacebook Prophet في التنبؤ بأسعار الإغلاق لسهم شركة Amazon - روابة, محمد (جامعة الوادي University of Eloued, 2024)
This study aimed to identify the best model for predicting the daily closing prices of Amazon's stock by comparing ARIMA models with the Facebook Prophet methodology during the period from 03/01/2023 to 17/07/2024. An ARIMA model and a Prophet model were built using the Python programming language, relying on its associated libraries, primarily pmdarima and prophet . The study concluded that the best model in terms of predictive ability is the ARIMA model, based on the error metrics used: MAE, MSE, and RMSE
Comparing the performance of the ARIMA and Facebook prophet methodologies in predicting closing prices for Amazon stock
Keywords: التنبؤ; أسعار الأسهم; نموذج ARIMA; منهجية Facebook prophet